Legal Policy for Peatland Protection - Zulkarnaini zulkarnaini (Fakultas Hukum Universitas Riau, 2020)
In 2015, Indonesia experienced the highest level of fire in the world, with more than 50 percent occurring on peatlands. This event put Indonesia in the spotlight on managing peatlands that were seen as ignoring commitments to reduce greenhouse gas emissions and prevent other fire losses, including school closures, respiratory problems and early deaths. This study analyzes peatland management policies in Indonesia in a legal perspective. This research uses a legal policy approach, which is an approach that is carried out by observing the laws and regulations relating to the policy issues studied. The results show that as a rule of law where government power is regulated by law, efforts to restore and protect peatlands in Indonesia are not optimal. Law enforcement support, including the establishment of new regulations regarding the spatial plan of peatlands which requires the preservation of protected peatlands as determined, has yet to materialize.